The Correlation of Digital Literation and STEM Integration to Improve Indonesian Students’ Skills in 21st Century - Dedi Riyan Rizaldi; Eris Nurhayati; Ziadatul Fatimah (International Journal of Asian Education, 2020)
Dynamic human development in the 21st Century demands students to make innovations in the world of education. Students are required to have 21st-century skills, namely creativity, critical thinking, collaboration, and communication. In contrast, teachers are required to have skills that must be mastered. The six capabilities are mastery of knowledge/content, mastery of 21st-century pedagogy, the ability of expertise in the development and achievement of students and give support, mastery of learning psychology skills; having counseling skills; and competence in using information technology and media. This article aims to discuss issues related to how to improve the ability of teachers and students to master 21st-century skills? Also, what extent is the role of digital literacy and STEM integration in improving 21st-century skills? This article using literature literacy methods sourced from international and national journals, books, and other relevant sources. Based on the study, it concluded that digital competence is not an absolute determinant of the development of 21st-century skills in students. Digital ability is a supporting factor for mastering 21st-century skills that should have been introduced and taught through schools. STEM learning with multidisciplinary mastery of science needs to be optimized in schools in Indonesia so that the expected learning objectives are in line with the demands of the 21st-century.